Different effects of amiodarone and dofetilide on the dispersion of repolarization between well-coupled ventricular and purkinje fibers - Árpádffy-Lovas Tamás (CANADIAN JOURNAL OF PHYSIOLOGY AND PHARMACOLOGY, 2021)
Increased transmural dispersion of repolarization is an established contributing factor to ventricular tachyar-rhythmias. In this study, we evaluated the effect of chronic amiodarone treatment and acute administration of dofetilide in canine cardiac preparations containing electrotonically coupled Purkinje fibers (PFs) and ventricular muscle (VM) and compared the effects to those in uncoupled PF and VM preparations using the conventional microelectrode technique. Dispersion between PFs and VM was inferred from the difference in the respective action potential durations (APDs). In coupled preparations, amiodarone decreased the difference in APDs between PFs and VM, thus decreasing dispersion. In the same preparations, dofetilide increased the dispersion by causing a more pronounced prolongation in PFs. This prolongation was even more emphasized in uncoupled PF preparations, while the effect in VM was the same. In uncoupled preparations, amiodarone elicited no change on the difference in APDs. In conclusion, amiodarone decreased the dispersion between PFs and VM, while dofetilide increased it. The measured difference in APD between cardiac regions may be the affected by electrotonic coupling; thus, studying PFs and VM separately may lead to an over-or underestimation of dispersion. © 2021, Canadian Science Publishing. All rights reserved.